Safety in Aviation and Space Technologies Select Proceedings of the 9th World Congress "Aviation in the XXI Century" - Bieliatynskyi, Andrii; Breskich, Vera.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of aerospace technology and aviation safety, as presented by researchers at the 9th World Congress (3z(BAviation in the XXI Century(3y(B: Safety in Aviation and Space Technologies, held in Kyiv, Ukraine, on April 26-28 2021. It covers highly diverse topics, including carbon neutral aviation, precision engineering in aerospace, robots in the aerospace industry, nanotechnology for aerospace, aircraft design and strength, tribotechnology in aviation, engines and power installations, intelligent robotic and measuring systems, control systems, civil aviation cybersecurity, mathematical modeling and numerical methods, aeronavigation, unmanned aerial complexes, environmental safety and aviation chemmotology, aviation transport logistics, and construction of transport facilities. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations. .s
Observations of LED Side Lights at the Stage of Visual Piloting -- Middleware Service for the Integration of Control Systems of the Aviation Engine and Aircraft -- Application of Fiber-optic Sensors for the Aircraft Structure Monitoring -- Iterative-Analytical Model of Nonlinear Deformation and Fracture of Multilayer Composite Panels -- Vibration Measurement Technologies and Systems -- Methods of Statistical Modeling of Atmospheric Turbulence -- Designing Integrated Cargo Delivery Systems on Logistics Principles -- Optimization of Parameters for the Printing Process of Adhesive Application in Honeycomb Core Manufacturing -- Rationalization of the Topology of Steel Combined Truss -- Construction of Analytical Coupling Model in Reinforced Concrete Structures in the Presence of Discrete Cracks -- Ergodesign Aspects of the Development of Unmanned Aerial Vehicle System -- Structural-Kinematic Analysis and Synthesis of Measuring Systems Using a Scanning Probe Microscope.
Keywords: Aerospace engineering; Astronautics; Transportation engineering; Traffic engineering; Control engineering; Robotics; Automation; Aerospace Technology and Astronautics; Transportation Technology and Traffic Engineering; Control, Robotics, Automation; Aerospace engineering -- Congresses; Aeronautics -- Safety measures -- Congresses